Two new cleistocheliferous species of Clathria of sciophilous habitats from Northeastern Brazil (Poecilosclerida: Demospongiae: Porifera) - Santos, George Garcia; Pinheiro, Ulisses (Zootaxa, 2014)
We describe two new species of Clathria (Microciona) Bowerbank, 1862: C. (M.) crassitoxa sp. nov. and C. (M.) trairae sp. nov. from Paraíba State (Northeastern Brazil). All are sciophilous species and are represented by small fragments removed from the substrate. Both new species have cleistochelae, and are compared with their cleistocheliferous congeners, differing from all of them by the possession of different combinations of other megascleres and microscleres.